135 The use of opioids in syringe drivers: an audit across 2 specialist palliative care services in the East Midlands Region. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Robinson, Rebecca; Chauhan, Alpna; England, Ruth; Boyland, Rebecca
Abstract : Background: There has been a recent increase in concern regarding the use of opioid medications in syringe drivers following the publicised report of the Gosport Inquiry, 2018. In our own clinical practice we have seen an increased anxiety and caution regarding syringe drivers, particularly in the community. Aim: To identify the average starting dose of opioids in syringe drivers for patients known to the Specialist Palliative Care Teams (SPC) across three settings; hospice, hospital and community. John Eastwood Hospice, Mansfield was the initial site in 2018 and a similar audit was conducted at Royal Derby Hospital in 2019. Standards: Our standards were taken from a number of sources, including the Palliative Care Formulary. For patients already on opioids, total daily dose should be appropriately converted to the opioid being used in the driver; for an opioid na¯ve patient, 10–20 mg morphine is suggested. Clinical judgement based on the patient's individual needs is vital. Method: Patients commenced on a syringe driver with an opioid across a 2-month period were identified; retrospectively in Mansfield, prospectively in Derby. Retrospective case note review was carried out using electronic and/or paper records. Results: The average (mean) starting dose of opioid in a syringe driver (morphine subcutaneous equivalent) prescribed or advised by SPC was 27 mg (range 2.5 mg–160 mg) in Mansfield, 21 mg (range 3.75 mg–80 mg) in Derby. All patients had a documented indication for both the use of an opioid and use of a syringe driver. Doses used were comparable to opioid use in the preceding 24 hours. Conclusions: The results from these audits are reassuring; demonstrating that when opioids in syringe drivers are used, the indication is considered, doses used are small compared to standards, and in the majority it is beneficial. The results between sites were similar, suggesting that practice is consistent across different areas of the region.